The British Identity and the Roots of British Euroscepticism - Bratanova, Kalina (Research Papers, 2018)
This paper aims to identify the aspects of Britishness that largely determine the typical of Great Britain Еuroscepticism. The identity of the world power is connected with the ideas of freedom and democracy, free trade, tolerance and commitment, as well as with the norms of sovereignty and good governance. These are a major factor for the unprecedented Brexit. On this basis, a theoretical model for the analysis of identity as a factor of the contemporary system of international relations has been constructed.
Keywords: Euroscepticism; Brexit; Identity